Separation of Deleterious Materials in Waste Water using Conventional and Recent Method through Adsorption Process: A Review - Norul Wahida, Kamaruzaman; Zularisam, A. W. (IRJET, 2016)
Pollutions around the world contribute to the water scarcity in clean water distribution. Clean water is very crucial for domestics and industrials activities. Purification through adsorption is one of the ways to produce clean water for consumption to meet the needs of the industries whether domestic or industrial necessity. Several purification techniques have been explored and adopted to meet the standard before distributed to the consumers. The adsorption technologies have been paid attention for the longest period due to its practicality and potential values which provides many advantages throughout the adsorption process. This review emphasized on the gravity separation, dissolved air floatation and membrane bioreactor system to remove deleterious materials includes chemical contaminants, particulates and suspended solidsin domestics and industrials waste water.